Pengaruh Usia Panen Terhadap Kualitas Daging Ayam Broiler Ditinjau Dari Kandungan Nutrisi Dan Tekstur - Hasanuddin, Andien Ayu Pratiwi; Rosdiyanyi (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the meat quality of broiler chickens at different harvest ages. Broiler chickens were raised in three different harvest age groups: 28 days, 35 days, and 42 days. The parameters measured included moisture content, fat content, protein content, as well as meat texture and taste. The results showed that the quality of broiler chicken meat tended to improve with increasing harvest age, especially in terms of protein content and meat texture. Chickens harvested at 42 days of age had higher fat content, but the meat texture was more tender compared to chickens harvested at 28 days. Therefore, selecting the right harvest age can affect the quality of the resulting broiler chicken meat.